Green Fluorescent Proteins (GFP) Induce Oxidative Stress in Normal Nasopharyngeal Cells Expression - Mohd Aminudin, Mustapha; Sim, Sai Peng (Japan University of Health Sciences & Japan International Cultural Exchange Foundation (JICEF), 2024)
Objective: To evaluate the effect of Green fluorescent proteins (GFP) expression on oxidative stress generation in normal nasopharyngeal cells. Material and Methods: pTracer vector that contained GFP expression and pcDNA transfected into normal nasopharyngeal cell line. Level of reactive oxygen species (ROS) will be assessed by measuring the fluorescence generated by the chemical 2',7'-Dichlorohydrofluorescein diacetate (DCFH-DA) for pcDNA and cell rox for pTracer. Association of GFP induce oxidative stress level in normal nasopharyngeal cell were calculated by comparing mean of pTracer and pcDNA gene by use independent Sample T test. Results: The association between oxidative stress and pTracer expression are statistically significant compared to pcDNA vector control cells. Conclusion: Our results show that, there are association of GFP expression in pTracer vector with oxidative stress production in normal nasopharyngeal cell thus support that GFP expression induce production of oxidative stress that mediated pathways in normal nasopharyngeal cell.